A CANONICAL AND THEOLOGICAL RECONSIDERATION OF THE DOCUMENT “THE IMPORTANCE OF FASTING AND ITS OBSERVANCE TODAY” OF THE HOLY AND GREAT COUNCIL OF CRETE - PERȘA, Răzvan (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
In this paper, I tried to examine the first four paragraphs of the document The Importance of Fasting and Its Observance Today, of the Holy and Great Council of Crete (2016), from a canonical and theological point of view, by taking into consideration its development, the pre-conciliary debates, and its final form. Having in mind this vast period of time needed for the final form of the text of the Holy and Great Council, we can assert the total victory of the theologians and circles with conservative theological visions, because the idea of changing and adapting fasting periods to current social circumstances was totally removed from the inter-Orthodox debate. The official document of the Holy and Great Council is an attempt of theological argumentation of the practice of fasting, highlighting, with several biblical and patristic quotations, the general importance of the institution of fasting, but without any practical clarification. The text contains more than 26 biblical, patristic and liturgical quotations. Almost 40% of the text of the document is represented by quotes and different references, showing a lack of originality and actuality. Despite that, the documents emphasizes that fasting in the Orthodox Church has many dimensions: historical-theological (fasting as divine commandment given in Paradise); ascetic-spiritual (fasting as great spiritual endeavor and the foremost expression of the Orthodox ascetic ideal); canonical (the foundation of fasting are the apostolic precepts, the synodal canons, and the patristic tradition as a whole); soteriological (the great significance of fasting for our spiritual life and salvation); and liturgical (fasting is according to the liturgical Tradition of the Orthodox Church, culminating with the Holy Eucharist).